Ecosystems in Slovakia. Issue 2 (9th December 2020) - Černecký, Ján; Gajdoš, Peter; Špulerová, Jana; Halada, Ľuboš; Mederly, Peter; Ulrych, Libor; Ďuricová, Viktória; Švajda, Juraj; Černecká, Ľudmila; Andráš, Peter; Rybanič, Rastislav
ABSTRACT: The authors have prepared a detailed map of Slovakia's ecosystems, which identifies individual ecosystems and their spatial distribution, status, and selected properties. The impetus for the production of this map is the need of various stakeholders, especially nature protection bodies, forestry management, agricultural management and public administration, for better data on the distribution of ecosystems. The methodology mostly involves using GIS analytical tools to combine datasets on nature protection, forestry, and agriculture which list attributes related to habitat identification. The results can be used for ecosystem services assessment, spatial planning, nature protection analysis, and other related purposes. The spatial precision of the data is determined by that of the field data, which was mostly created at scales between 1:10000 and 1:5000. The data are stored in the form of a geodatabase containing more than 1, 000, 000 polygons.